Relationship Between the Risk of Postpartum Depression and the Quality of Mother-Infant Bonding Attachment in Postpartum Mothers - Septyana Nur Ernawati; Faizah Betty Rahayuningsih (Adi Husada Nursing Journal, 2025)
The postpartum period is a critical phase for establishing mother–infant bonding, and untreated postpartum depression (PPD) may disrupt this process and affect infant development. This study examined the association between PPD risk and bonding quality among postpartum mothers. A cross-sectional quantitative design was applied to 92 respondents selected through simple random sampling at Miri and Tlogowungu Community Health Centers, with data collection conducted from August to September 2025. PPD risk was assessed using the Edinburgh Postnatal Depression Scale (EPDS), and bonding quality was measured using the Postpartum Bonding Questionnaire (PBQ). Data were analyzed using the Chi-Square test, with association strength reported as Odds Ratio (OR) and a 95% Confidence Interval (CI). Results showed that 31.5% of mothers were at risk for PPD. Normal bonding was identified in 72.8%, while 27.2% experienced bonding disturbances, including 18.5% with severe impairment and 8.7% with mild disruption. A significant association was observed between PPD risk and bonding disturbance (p < 0.001). Mothers at risk of PPD were substantially more likely to experience severe bonding impairment compared with those not at risk (OR = 100.9; 95% CI: 16.1 – 632.2). These findings indicate that PPD risk is strongly associated with impaired maternal–infant bonding, underscoring the need for routine screening and early psychosocial support in postpartum care.